PTU-220 Laparoscopic protack rectopexy for the management of full thickness rectal prolapse. (22nd June 2015) - Karim, A; Cubas, V; McArthur, D
Abstract : Introduction: Full thickness rectal prolapse (FTRP) tends to more commonly affect elderly women. Treatment options are surgical, either abdominal or perianal procedures; the latter have been preferred in elderly patients with comorbidity due to their perceived lower risk. However, recent advances in laparoscopy have enabled minimally invasive abdominal operations to be performed. Laparoscopic ventral rectopexy has been suggested as a safe option in the elderly cohort of patients; however, there is growing concern about mesh complications, and the operation takes well over an hour, even for surgeons with vast experience. We present a series of patients treated with "laparoscopic Protack rectopexy (LPR)" for FTRP. Method: A consecutive series of patients presenting with FTRP were treated with LPR. The technique mimics that of suture rectopexy, with full rectal mobilisation from the sacral promontory to the pelvic floor followed by fixation of the lateral mesorectal peritoneum to the sacral promontory with 4–6 5 mm Protacks. Demographics, length of operation and stay, short and long term complications and functional outcomes were assessed. Results: 16 consecutive patients with FTRP underwent LPR. M:F ratio of 1:15 with mean age 83 and ASA grades 1 (n = 1), 2 (9), and 3 (6). Mean length of operation was 27 min, range 13–52 mins. Median length of stay was 4 days. One patient had urinary retention after trial without catheter, but there were no other short term complications. Patients were followed up for median 6 months. There was one full thickness recurrence at 3 years in a 90 year old, subsequently treated with Delorme's, and one patient had a small mucosal prolapse managed conservatively. One patient reported worsening of constipation, although her predominant symptom preoperatively was incontinence that improved postoperatively, whilst 3 patients reported an improvement in continence. Conclusion: LPR is a safe technique that can be performed quickly and effectively for patients with FTRP. It appears to have acceptably low recurrence rates and offers good functional outcomes to patients who have historically been treated with perineal procedures. Disclosure of interest: None Declared.